2004
DOI: 10.1007/s10067-003-0817-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the involvement of the distal interphalangeal joint in psoriatic patients related to nail psoriasis?

Abstract: The aim of this study was to investigate the relationship between onychopathy and distal interphalangeal (DIP) joint involvement in psoriatic patients. Twenty-five consecutive unselected, unrelated patients with psoriatic onychopathy and 25 consecutive unselected, unrelated patients with psoriatic arthritis without onychopathy, were enrolled in the study. X-ray films of the hands were taken to identify DIP arthritic involvement and/or bone changes of the distal phalanx, which were categorized into five classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 7 publications
3
32
0
1
Order By: Relevance
“…Scarpa et al revealed the relationship between DIP arthritis and the duration of onychopathy in PsA [16]. However, most of the PsA patients pay little awareness to their nail conditions.…”
Section: Study Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Scarpa et al revealed the relationship between DIP arthritis and the duration of onychopathy in PsA [16]. However, most of the PsA patients pay little awareness to their nail conditions.…”
Section: Study Limitationsmentioning
confidence: 98%
“…Plain radiographs of bilateral hands were taken to detect and define PsA bony changes in distal interphalangeal (DIP) joints [14,16]. Radiographs are useful for identifying typical proliferative and destructive bone lesions in PsA [14,16].…”
Section: Radiography Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, we hypothesised that the involvement of the nail matrix by the inflammatory process might contribute to lesions such as pitting in a linear pattern consistent with the ‘finger-like’ attachment of the ligamentous structures linking the nail to the extensor tendon and distal interphalangeal joint capsule [16]. …”
Section: Introductionmentioning
confidence: 99%
“…A study by Williamson and colleagues assessed 69 patients with PsA and found correlations between nail disease severity and skin disease, enthesitis, polyarticular disease, HAQ score, higher depression and anxiety scores, and unremitting and progressive arthritis 4 . Scarpa and colleagues found a relationship between distal interphalangeal (DIP) arthritis in patients with PsA and the duration of nail psoriasis, although there was not a statistically significant correlation between the distribution of DIP arthritis and onychopathy 5 .…”
Section: To the Editormentioning
confidence: 99%